One-Pot Synthesis of Nuevamine Aza-Analogues by Combined Use of an Oxidative Ugi Type Reaction and Aza-Diels–Alder Cycloaddition - Islas-Jácome, Alejandro; Gutiérrez-Carrillo, Atilano; García-Garibay, Miguel A.; González-Zamora, Eduardo (Synlett, 2014)
A rapid and efficient one-pot synthesis of a series of four novel nuevamine aza-analogues is described based on the oxidative Ugi-type reaction and aza-Diels–Alder reaction as post-functionalization. A simple IBX-mediated oxidation of a secondary amine followed by isonitrile α-addition and finally an aza-Diels–Alder cycloaddition provides the desired compounds in excellent overall yields considering the short reaction time, atom economy, and the molecular complexity of the final products. This protocol presents a highly attractive procedure for the rapid generation of fused polyheterocycles.
Keywords: one-pot synthesis; natural products; oxidation; oxidative Ugi reaction; aza-Diels–Alder cycloaddition